(untitled) - García González, Fco. Javier (Florentia Iliberritana, 2016)
We are abording in the present work the epystemologic term δοkϵιv, its syntactic and lexemic caracteristics being analyzed and structured in trhee meaning blocks (i. e. APPEARENCE, BELIEVING, OPINION-DECISION) and two planes (SUBJECTIVE, OBJETIVE). We propose the formal mechanisms for their differentation (Appearing or not appearing of "dativus iudicantis", Negation ’s Transportation and Subject Rising) and the posible changes involved.